Accumulation and phytotoxicity of perfluorooctanoic acid and 2, 3, 3, 3-tetrafluoro-2-(heptafluoropropoxy)propanoate in Arabidopsis thaliana and Nicotiana benthamiana. (April 2020) - Chen, Chih-Hung; Yang, Shih-Hung; Liu, Yina; Jamieson, Pierce; Shan, Libo; Chu, Kung-Hui
Abstract: 2, 3, 3, 3-Tetrafluoro-2-(heptafluoropropoxy)propanoate (known as GenX) has been used as an alternative to perfluorooctanoic acid (PFOA) which was phased out of formulations for industrial and consumer product applications in 2015. While the effects of GenX on lab animals have been studied, little is known about its effects on plants. This study examined and compared the accumulation and toxicity of GenX and PFOA in the model plants Arabidopsis thaliana and Nicotiana benthamiana . Both plants showed reduction in biomass and root growth following exposure to PFOA or GenX in a dosage-dependent manner. The bioaccumulation factors (BFs) of GenX and PFOA were plant species-dependent, with higher BFs in A. thaliana compared to N. bethanminana . Additionally, GenX and PFOA were more readily accumulated into shoot tissues of A. thaliana than in N. bethanminana . Exposure to GenX also caused a reduction in chlorophyll content (18%) and total phenolic compounds (26%). However, GenX exposure increased superoxide dismutase activity and H2 O2 content (1.6 and 2.6 folds increase, respectively) in N. benthamiana . Overall, our result suggest that GenX is bioaccumulative, and that its accumulation likely inhibits plant growth and photosynthesis as well as inducing oxidative stress. Graphical abstract: Image 1 Highlights: GenX and PFOA inhibit growth of A. thaliana and N. benthamiana. Bioaccumulation and translocation of GenX and PFOA are plant species-dependent. Bioaccumulation factor of GenX is higher in A. thaliana than in N. benthamiana. GenX decreases chlorophyll content and triggers oxidative stress in N. benthamiana.